The Influence of Business and Credit Characteristics on Bank Credit by Traders at Pasar Horas of Pematangsiantar City - Tumpal Manahara Siahaan; Herlina H Sianipar (Jurnal Mantik, 2020)
Study aims to determine the influence of business and credit characteristics on Bank credit by traders at Pasar Horas of Pematangsiantar City. The type of research used is quantitative research with descriptive data analysis approach and data collection using research instruments, quantitative statistical data analysis with the aim of testing predetermined hypotheses. The result of the study show the effect of Business and Credit Characteristics simultaneously affect the bank credit return variable by 76.4%. The Effect of Business characteristics on Bank Credit Returns show tcount 5,688 which is bigger than t table which is equal to 1,988, and level the significance is 0.000 <0.05, so that ????0 is rejected ????1 is accepted means business characteristics have a significant effect on bank credit repayments by traders. The Effect of Credit Characteristics on Credit Return obtained from the t test (partial) which shows that t count (17.486) is greater than t table (1.988) so that ????0 is rejected ????1 is accepted means the credit characteristics affect the repayment of bank by Traders in Pematangsiantar City. If the variable of credit characteristics is higher the assumption of the variable credit characteristics return in bank will increase.